VALUASI EKONOMI SUMBER DAYA ALAM DAN LINGKUNGAN SEKTOR PERTAMBANGAN DALAM PENYUSUNAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) HIJAU DI KABUPATEN KETAPANG - B61111015, KRESSENSIANA KUSNAWATY (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT The research was based on the use of natural resources mining sector by the government to boost economic growth in Ketapang Regency, which resulted in the depletion and environmental degradation. Based on the facts, the research is focused on calculating the value of depletion and degradation of the mining sector in Ketapang Regency with the economic valuation instruments and also the Green GDP calculation is done right from the year 2007 until the year 2011, which has not been factored into GDP Chocolate that has yet to show the value of social welfare as desired in the green economy principles. The purpose of this study was to: 1) analyze the value and the GDP growth rate in the mining sector Green Ketapang Regency. 2) Calculate and analyze how much the rate of natural resource depletion and environmental degradation of the mining sector to GDP Green Ketapang Regency. The method used in this study was descriptive, using secondary data obtained from the data and data mining GDP Brown Ketapang Regency. While this type of data used is panel data (pooled data) and cross data (cross section). Based on available data and then do the economic valuation of natural resources and mining sector environment , using quantitative and qualitative analysis tools , then the Green GDP calculation is done using the benefit transfer method . Variables used in this study consisted of ; GDP Brown , Spring Green GDP , Depletion of natural resources , Unit Rent, environmental degradation and the Green GDP . The results obtained by the fact that the author, in which the value of depletion and degradation caused by mining activities tend to increase annually between Green GDP value even mining sector from 2007 to 2011 minus Rp.57.215, 898 billion to the GDP value in the Ketapang regency Brown 2007 to 2011, meaning that the mining sector's contribution to regional development Ketapang is smaller than the value of the damage. Based on the results, it can be concluded that GDP Brown mining sector in Ketapang Regency from 2007 to 2011 continued to increase. However, if viewed from the side of Green GDP, the value minus growth in the amount experienced depletion and degradation due to mining commodity production occurs. This means the economic value generated in the mining sector tends to shrink compared to the value of the damage. Keywofds: Economic Valuation, Depletion, Degradation, Green GDP.